Analysis of Factors Relating The Quality of Nursing Care Documentation - Fatmawati, Fatmawati; Febrianti, Yola; Rahmayanti, Fenita; Rusmanwadi, Rusmanwadi; Windureswari, Windureswari (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background: Effective documentation can help prevent various issues experienced by patients in hospitals. By maintaining thorough, systematic, and accurate records, nurses can mitigate the risk of errors and ensure the continuity of care. This research seeks to identify the factors influencing the quality of nursing care documentation in accordance with the Indonesian Nursing Diagnostic Standards (SDKI), Indonesian Nursing Outcome Standards (SLKI), and Indonesian Nursing Intervention Standards (SIKI) at Dr. M Djamil General Hospital in Padang in 2023. Methods: This research employed a cross-sectional study design. The study population comprised all nurses working in the inpatient unit of Dr. M. Djamil General Hospital Padang. The sampling technique used in this research was proportional random sampling, and the sample size consisted of 238 respondents. Results: The research results indicated that 61.3% of the documentation quality was deemed inadequate, with 63% lacking in knowledge, 61.8% exhibiting poor attitudes, 57.6% demonstrating low motivation, 68.9% experiencing insufficient supervision, and 57.1% showing inadequate socialization. The study found significant relationships between knowledge, attitude, supervision, and socialization with the quality of nursing care documentation, with a p-value of <0.005. The factor most strongly associated with the quality of nursing care was socialization (OR = 2.019, 95% CI 1.045-3.901). Conclusion: This research identified that the quality of nursing documentation was still suboptimal, highlighting the ongoing need for continuous and intensive socialization regarding the documentation of nursing care.